Information-Psychological Impact as an Important Factor Determining the Degree of Combat Activity of Servicemen - Baghdasaryan, Svetlana (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
Significant increase in the role of information (psychological) actions and military importance of information and propaganda operations in modern warfare have fundamentally changed the nature of warfare, having the aim to influence the leadership of the enemy state, the state of mind of specific people, the moral and psychological state of the armed forces, as well as the positions and emotional state of the entire population with few resources, without the use of military force. It is no coincidence that in modern warfare "the center of gravity" became the intellectual abilities, emotional and volitional qualities of servicemen of the enemy’s Armed Forces in order to reduce combat activity and the importance of the goal by creating a sense of moral exhaustion, incapability, anxiety, neuropsychological instability. The purpose of this article is to comprehensively study the role and significance of information-psychological influence in modern warfare, to demonstrate its impact on the combat activity of servicemen. To achieve the goal we used the following methods of interdisciplinary theoretical analysis: comparative, generalized, coordination. As a result of the study we came to the conclusion that in modern warfare the outreach and psychological activities are of paramount importance, which makes it possible to achieve the desired end state with few resources even before the start of hostilities. One of the important factors contributing to the increase of combat activity of servicemen, reliability of information and protection from negative information-psychological impact can be realized in the course of battle, including psychological training.